SURVEI TINGKAT KESEGARAN JASMANI SISWA YANG MENGIKUTI EKSTRAKURIKULER PENCAK SILAT DAN SISWA YANGÂ MENGIKUTI EKSTRAKURIKULER FUTSAL (STUDI PADA SMAN 1 SUKODADI, LAMONGAN) - DWI WIDYATMOKO, SANTYO (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Sport is an activity that closely related with human live that connected with its own physical and spiritual. Sport activity is one of the best alternatives to avoid from lack of movement and and as an effort to keep the physical fitness. However, in this modern live sport have little forgetted since the demand of live on the society. In the implementation process of physical education at school have purpose to assisst student improve their physical fitness and health. The existence of physical education at school is one of the efforts to improve physical fitness on education environment. Beside physical education at school that must be followed, studnet also obligated to follow one of the extracurricular activities, since ectracurricular can be an area in imporve student skill. This research aim to find out how and what level of student physical fitness who following pencak silat extracurricualr and the physical fitness of student who following futsal extracurricular. Sample collection conducted by random sampling method. In this researcg applying survey research (one shot model) namely research that give description or depiction of a condition as clear as possible without treatment  to subject who have researched. Population in this research is all student of senior high school of 1  Sukodadi who following pencak silat and futsal extracurricular, with data collection using TKJI (Indonesian Physical Fitness Test). Based on the research result, it found that the mean of student who following pencak silat extracurricular as big as 13.87 with standard deviation 1.776 while student who follow futsal extracurricular mean is 14.37 with standard deviation ,9999. By calculation through SPSS for windows evaluation 20, so the analysis result of physical fitness of student who following pencak silat extracurricular is low, while the physical fitness of student who following futsal extracurricular is medium. Keywords : physical fitness, extracurricular, pencaksilat and, futsal.